[Translated article] Oral Supplementation and Systemic Drugs for Skin Aging: A Narrative Review - D. Morgado-Carrasco; J. Gil-Lianes; E. Jourdain; J. Piquero-Casals (Actas Dermo-Sifiliográficas, 2023)
Skin aging is influenced by intrinsic and extrinsic factors and involves multiple pathogenic mechanisms. The most widely used treatments are topical products and minimally invasive procedures. Evidence on the benefits of systemic therapy is limited for several reasons: reliance on mostly small and predominantly female samples, short study durations, methodologic heterogeneity, and a lack of consensus on which outcome measures are clinically relevant. Furthermore, systemic drugs and oral supplements are not without adverse effects. Oral hydrolyzed collagen and oral hyaluronic acid are well tolerated, and numerous clinical trials show they can mitigate some signs of skin aging. Low-dose oral isotretinoin is another option, but it has a higher risk of adverse effects. Evidence is lacking on the effects of the many dietary supplements on offer, such as vitamins, flavonoids, plant extracts, and trace elements. The future of skin aging management would appear to lie in the use of senolytic and senomorphic agents targeting senescent cells in the skin. Resumen: El envejecimiento cutáneo está influido por factores intrínsecos y extrínsecos y múltiples mecanismos patogénicos están involucrados. Los tratamientos utilizados en la actualidad son sobre todo tópicos o son procedimientos mínimamente invasivos. La evidencia sobre la utilidad de la terapia sistémica es limitada: los estudios son en su mayoría de pequeño tamaño, de reducida duración, incluyen a mujeres de manera mayoritaria, la metodología de evaluación es heterogénea y no hay parámetros consensuados de respuesta clínica relevante. Además, los suplementos o fármacos sistémicos no están exentos de efectos adversos. El colágeno hidrolizado oral y el ácido hialurónico oral son bien tolerados y múltiples ensayos clínicos muestran que pueden mitigar algunos signos de envejecimiento cutáneo. La isotretinoína oral en dosis bajas es otra alternativa, pero con un mayor potencial de efectos adversos. Múltiples suplementos, como vitaminas, flavonoides, diversos extractos de plantas y oligoelementos presentan escasa evidencia clínica. El futuro del manejo del envejecimiento cutáneo parece ser el tratamiento con agentes senolíticos o senomórficos dirigidos específicamente contra células cutáneas senescentes.